Covid-19 containment policies in Nigeria: the role of conflictual federal–state relations in the fight against the pandemic. Issue 169 (3rd July 2021) - Aniche, Ernest Toochi; Iwuoha, Victor Chidubem; Obi, Kelechukwu Charles
SUMMARY: This briefing explores how the administrative fight against Covid-19 in Nigeria, particularly the conflictual political economy of federalism in this mono-product/oil-dependent economy, has shaped the making and implementation of virus containment policies and strategies. The analysis shows that the disconnects between the federal and state governments have blocked a harmonised and coordinated containment response. Instead, the measures to manage the pandemic have worsened the already highly conflictual – as well as dependent and centripetal – intergovernmental fiscal relations between federal and state governments, and among state governments.